Implementasi Enterprise Resource Planning Odoo Menggunakan Metode Analisis Proses Bisnis As-Is dan To-Be - Azahra, Nava; Aszava, Aliya; Maulana, Muhammad Fajar; Andreyan, Syahrul Bagus; Supriyono, Supriyono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The implementation of an Odoo-based Enterprise Resource Planning system is considered a relevant solution to address operational problems faced by small and medium-scale retail businesses that still rely on manual systems. This study aims to analyze existing business processes, identify operational issues, and design as well as evaluate the implementation of an Odoo-based Enterprise Resource Planning system to improve operational efficiency and data management accuracy in grocery retail businesses. The research methods employed include field observation, structured interviews, and documentation studies to obtain a comprehensive understanding of the Sales, purchasing, and inventory management processes that are currently conducted manually. Business process analysis was carried out using the As-Is and To-Be approach to identify gaps between the existing conditions and the ideal conditions supported by an integrated system. The results indicate that the implementation of Odoo ERP using the Sales, Inventory, and Purchase modules successfully automates the recording of Sales and purchasing transactions, updates inventory data in real time, and integrates all operational activities into a centralized system. The implemented system effectively reduces the risk of data entry errors, improves inventory data accuracy, and accelerates the generation of operational reports that can be accessed in real time through the dashboard. System evaluation shows that inter-module integration functions properly and supports faster, data-driven decision-making. However, the study also reveals that optimal system utilization requires additional user training and continuous assistance to ensure that all ERP features can be fully utilized.